Neonatal cholestasis - differential diagnoses, current diagnostic procedures and treatment - Thomas eGötze; Holger eBlessing; Christian eGrillhösl; Patrick eGerner; André eHoerning (Frontiers Media S.A., 2015)
Cholestatic jaundice in early infancy is a complex diagnostic problem. Misdiagnosis of cholestasis as physiologic jaundice delays the identification of severe liver diseases. In the majority of infants it may represent benign cases of breast milk jaundice, but few among them are masked and caused by neonatal cholestasis that requires a prompt diagnosis and treatment. Therefore, a prolonged neonatal jaundice longer than two weeks after birth must always be scrutinized because an early diagnosis is essential for appropriate management. To rapidly identify the cholestatic cases, the conjugated bilirubin needs to be determined in any infant presenting with prolonged jaundice at 14 days of age with or without depigmented stool. Once neonatal cholestasis is confirmed, a systematic approach is the key to reliably achieve the diagnosis in order to promptly initiate the specific, and in many cases, life saving therapy. This strategy is most important to promptly identify and treat infants with biliary atresia, the most common cause of neonatal cholestasis that requires a hepatoportoenterostomy as soon as possible.Here, we provide a detailed work-up approach including initial treatment recommendations and a clinically oriented overview of possible differential diagnoses in order to facilitate an early recognition and a timely diagnosis. This warrants a broad spectrum of diagnostic procedures and investigations including new methods that are described in this review.